Strategic leadership according to the four Brahmavihāra principles in the Chiang Mai Primary Educational Service Area Office 1 - วรพงศ์พัชร์ ณฐาพัชร์; Sriaroon, Supaporn (วิทยาการบริหารภาครัฐสมัยใหม่, 2024)
This research aims to achieve the following objectives: (1) to examine the conditions and challenges associated with strategic leadership grounded in the four Brahmavihāra principles among educational institution administrators under the jurisdiction of the Chiang Mai Primary Educational Service Area Office, Area 1; and (2) to compare the strategic leadership practices based on these Brahmavihāra principles among the administrators. The study sample comprised 70 academic department heads from educational institutions within the Chiang Mai Primary Educational Service Area Office, Area 1, selected using simple random sampling. Data were gathered through questionnaires and analyzed using descriptive statistics, including percentages, means, and standard deviations. The analysis also involved t-tests to compare differences and content analysis to interpret the findings. The results indicate that: Strategic leadership, as informed by the four Brahmavihāra principles, is practiced at a high level across all aspects among the administrators in Chiang Mai Primary Educational Service Area Office, Area 1. When considering individual principles, the levels were uniformly high, with kindness and compassion being the most prominent, followed by sympathetic joy (mudita) and equanimity. The strategic leadership practices based on the Brahmavihāra principles did not show significant differences when classified by educational level and work experience.